A comparison of some potential indicators of desiccation-tolerance in 2 Poikilochlorophyllous Xerophyta species and Homiochlorophyllous Craterostigma wilmsii - Brown, Carly (Department of Biological Sciences, 2017)
Three possible indicators of desiccation-tolerance in ang10sperms: sucrose accumulation and hexose sugar flux, an increase in hexokinase activity, and accumulation of LEA-like proteins, were investigated and compared during dehydration between two moncotyledonous poikilochlorophyllous resurrection angiosperm species; Xerophyta schlecterii and Xerophyta humilis, and a dicotyledonous homiochlorophyllous resurrection species, Craterostigma wilmsii. Comparisons were also made with Xerophyta viscosa, using data from Whittaker et al, (2001). Soluble sugar concentrations and hexokinase activities were also examined during rehydration of the three species. Sucrose was accumulated during dehydration in all species examined. However, C. wilmsii had completed sucrose accumulation by the intermediate stages of drying, whereas Xhumilis exhibited a late accumulation. It was not clear if Xschlecterii exhibited late sucrose accumulation due to high standard deviations in the results. C. wilmsii accumulated higher sucrose levels than the two poikilochlorophyllous species. During rehydration the sucrose concentrations dropped in all three species, and was probably being used as an energy source for the resumption of metabolism. Glucose and fructose concentrations were relatively constant during dehydration in all three species, and did not appear to be contributing greatly to sucrose accumulation. This was further confirmed by the low levels of activity of hexokinase found in all three species during dehydration and rehydration, which suggests that the channelling of glucose and fructose into sucrose biosynthesis is not being upregulated during dehydration. C. wilmsii had an increased level of hexokinase late in dehydration, that may have been in preparation for the rapid rehydration experienced by this homiochlorophyllous species, where hexokinase would need to rapidly channel glucose and fructose into metabolism. There was not an increase in activity at the period of highest sucrose accumulation in this species. The activity of hexokinase was relatively constant throughout dehydration and rehydration for Xschlecterii, as it was for Xhumilis. Glucose and fructose levels dropped slightly in C. wilmsii during rehydration but remained relatively constant in the two poikilochlorophyllous species. The presence of LEA-like proteins was found in all three species, although the bands were very faint for X viscosa and Xhumilis. In Xschlecterii the bands were clear in the dehydrated leaf sample, but were faint or absent in the hydrated sample. It is possible that the proteins in this species were upregulated or induced by drying. A protein common to all three species in dehydrated and hydrated samples was observed between the 22.5 kDa and the 15.3 kDa molecular markers.